2019
DOI: 10.3390/sym11081038
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Mathematical Modeling of Electro-Osmotic Couette–Poiseuille Flow of MHD Power-Law Nanofluid with Entropy Generation

Abstract: The basic motivation of this investigation is to develop an innovative mathematical model for electro-osmotic flow of Couette–Poiseuille nanofluids. The power-law model is treated as the base fluid suspended with nano-sized particles of aluminum oxide (Al2O3). The uniform speed of the upper wall in the axial path generates flow, whereas the lower wall is kept fixed. An analytic solution for nonlinear flow dynamics is obtained. The ramifications of entropy generation, magnetic field, and a constant pressure gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…Energy and mass exchange has attracted the attention of contemporary researchers due to its diverse uses such as in cancer therapy, sensors, drying processes, MHD generators, the cooling of nuclear reactors, high temperature plasmas, etc. Recently, Ellahi et al [32] investigated the magnetohydrodynamic flow of nanofluid with entropy generation numerically. Moreover, numerical simulation of MHD mixed convection nanofluid flow was conducted by Khan et al [33].…”
Section: Introductionmentioning
confidence: 99%
“…Energy and mass exchange has attracted the attention of contemporary researchers due to its diverse uses such as in cancer therapy, sensors, drying processes, MHD generators, the cooling of nuclear reactors, high temperature plasmas, etc. Recently, Ellahi et al [32] investigated the magnetohydrodynamic flow of nanofluid with entropy generation numerically. Moreover, numerical simulation of MHD mixed convection nanofluid flow was conducted by Khan et al [33].…”
Section: Introductionmentioning
confidence: 99%
“…Asadollahi et al [40] deliberated the phase change of a fluid in a square microchannel. The most relevant and new studied studies can be reads in Ellahi et al [41][42][43], Bhatti et al [44], Ameen et al [45], Vo et al [46], Ahmad et al [47], Sheikholeslami et al [48], Ali et al [49], and Ullah et al [50].…”
Section: Introductionmentioning
confidence: 99%
“…Zeeshan et al [36] reported the effect of radiative nanofluid flow under a pressure gradient due to entropy generation and observed an increase in entropy with an increase in the pressure gradient. Ellahi et al [37] investigated flow of a power-law nanofluid with entropy generation and noted that the skin friction coefficient increases at the heated wall. Yousif et al [38] analyzed the momentum and heat transfer of MHD Carreau nanofluid over an exponentially stretching surface and used the shooting method to compute the solution.…”
Section: Introductionmentioning
confidence: 99%